Epithelial Cell Apoptosis in Recurrent Aphthous Ulcers. (July 2015) - Al-Samadi, A.; Drozd, A.; Salem, A.; Hietanen, J.; Häyrinen-Immonen, R.; Konttinen, Y.T.
A recurrent aphthous ulcer (RAU) is a common inflammatory ulcerative lesion affecting oral mucosa. We studied the eventual apoptosis of epithelial cells from the point of view of ulcer and inflammation. RAU lesions and healthy mucosa samples were immunostained for caspase-3 and high-mobility group box 1 (HMGB1). DNA nicks were identified using TUNEL staining. We studied the effects of tumor necrosis factor α (TNFα) and interferon γ (IFNγ) on the toll-like receptor 2 and 4 (TLR2 and TLR4) expression of human oral SCC-25 keratinocytes. We also studied the effects of self-DNA, all-thiol-HMGB1, and disulfide-HMGB1 on epithelial cells, with or without IFNγ. At the edge of RAU lesions, all epithelial cell layers were caspase-3 +, TUNEL +, and HMGB-1 + and had widened intercellular spaces. In contrast, healthy epithelial cells were negative for caspase-3 and TUNEL staining. HMGB1 was seen in only the basal cell layers, and the cells retained close cell-to-cell contacts. Self-DNA increased TNF-α mRNA ( P = 0.02) in SCC-25 cells. Both TNFα and IFNγ ( P = 0.01) increased TLR2. Upon TNFα stimulation, SCC-25 cells lost their nuclear HMGB1 staining. HMGB1 did not increase IL-8, IL-6, or TNF-α mRNA in SCC-25 cells, which was unaffected by the presence of IFNγ. We conclude that in healthy epithelium, the most superficial cells at the end of their life cycle are simply desquamated. In contrast, RAU is characterized by top-to-bottom apoptosis such that dead cells may slough off, leading to an ulcer. Because of a lack of scavenging anti-inflammatory macrophages, apoptotic cells probably undergo secondary necrosis releasing proinflammatory danger signals, which may contribute to the peripheral inflammatory halo. This is supported by self-DNA-induced TNFα synthesis. In contrast to TLR4- and TLR2-binding lipopolysaccharide used as a positive control, disulfide-HMGB1 did not stimulate proinflammatory cytokines.